Enhancement of aerobic rice cultivar by effective microorganisms application at different growth stages / Syed Muhamad Syahir Syed Azmi - Syed Azmi, Syed Muhamad Syahir (Faculty of Plantation and Agrotechnology, 2019)
Rice cultivation by using effective microorganism (EM) at different growth stages may enhance the productivity of paddy growth under aerobic condition. The objectives of this study were to observe the effect of EM application on aerob paddy cultivation at different series of harvesting and to deter-mine the plant growth parameters for each of the treatment at difference growth stages. The cultivar of Aeron 1 was obtained from MARDI, Penang. The treatment for this study was T1= 1.8 g NPK with urea (control) while T2 and T3 treatment was applied with 100 mL of EM respectively during 15 (early vegetative stage) and 45 DAS (late vegetative stage). The RCBD experimental design was used with two replications in each treatment in four blocks. There are three series of harvesting (35, 50 and 60 DAS) was conducted throughout this study. The growth parameter studied was shoot and root dry biomass, number of tillers, RGR at each of harvesting. The overall results showed that there was no significant difference occurred between treatments applied. However, the growth pattern of T2 (100mL EM at 15 DAS) increasing earlier in terms of plant biomass and numbers of tillers compare to other treatment (T1 and T3). In conclusion, the application of EM at different growth stages are not enhance the plant growth of Aeron 1 under aerobic cultivation.